2012
DOI: 10.1155/2012/258502
|View full text |Cite
|
Sign up to set email alerts
|

Some Notes on the Difference Equation xn+1=α+(xn−1/xnk)

Abstract: We investigate the behavior of the solutions of the recursive sequence  xn+1=α+xn-1/xnk,  n=0,1,…, whereα∈[0,∞),k∈(0,∞),and the initial conditionsx-1,x0are arbitrary positive numbers. Included are results that considerably improve those in the recently published paper by Hamza and Morsy (2009).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In Figure 3 we illustrate the result of Theorem 11 for = 3, = 2, and = 0.5, with the initial conditions −1 = 0.7, 0 = 0.54 and choosing = 0.2; in this case the subsequence ( 2 ) of the solution of (1) is bounded with 0.5 < 2 < 0.7 for all ≥ 0, while the subsequence ( 2 +1 ) is unbounded, so the terms of ( 2 ) appear approximately zero in comparison with the terms of ( 2 +1 ). Also Figure 4 explains the same result for = 0.3, = 2, and = 1.5; Gümüs andÖcalan in [5] showed that when > 1 and → ∞, every solution of (1) is unbounded. Figure 5 gives a counter example of this result for = 10 10 , = 1, and = 1.1.…”
Section: Global Behavior Of Solutions and Boundednesssupporting
confidence: 62%
See 3 more Smart Citations
“…In Figure 3 we illustrate the result of Theorem 11 for = 3, = 2, and = 0.5, with the initial conditions −1 = 0.7, 0 = 0.54 and choosing = 0.2; in this case the subsequence ( 2 ) of the solution of (1) is bounded with 0.5 < 2 < 0.7 for all ≥ 0, while the subsequence ( 2 +1 ) is unbounded, so the terms of ( 2 ) appear approximately zero in comparison with the terms of ( 2 +1 ). Also Figure 4 explains the same result for = 0.3, = 2, and = 1.5; Gümüs andÖcalan in [5] showed that when > 1 and → ∞, every solution of (1) is unbounded. Figure 5 gives a counter example of this result for = 10 10 , = 1, and = 1.1.…”
Section: Global Behavior Of Solutions and Boundednesssupporting
confidence: 62%
“…they investigated the behavior of positive solutions of (15); they proved that when > 1, every positive solution of (15) is bounded and when > 1/ ≥ 1, the equilibrium point of (15) is globally asymptotically stable and they showed that (15) has periodic solutions without conditions on and . These results are improved in [5] by Gümüs andÖcalan; they investigated the boundedness character of positive solutions of (15); they proved that if 0 ≤ < 1, then there exist unbounded solutions of (15) in the cases when ∈ (0, ∞) and → 0 + or > 1 and → ∞; then every positive solution of (15) is unbounded. When 0 + , ∞, and > 1, then every positive solution of (15) is bounded.…”
Section: Remark 7 (I) Is Locally Asymptotically Stable If and Only Ifmentioning
confidence: 98%
See 2 more Smart Citations